Respon Perendaman PGPR Dan Dosis Pupuk Kandang Terhadap Pertumbuhan Dan Hasil Mentimun (Cucumis sativus L.) - Kasim, Nursidah; Kahar, Kahar; Hayatudin, Hayatudin (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2025)
The problem of good plant nutrition is still a question mark, the use of fertilizer and PGPR can increase plant growth and yield. This study aims to determine the effect and interaction of seed soaking using PGPR and chicken manure doses on the growth and yield of cucumbers. This study was carried out on land owned by residents in Tambun Village, Tolitoli Regency, Central Sulawesi Province, using a Randomized Block Design (RAK) factorial treatment, namely the first factor of seed soaking consisting of 3 levels, namely: W0 (control), W1 (4 hours), W2 (6 hours). The second factor, the dose of chicken manure consisting of 3 levels, namely: D0 (control), D1 (3 kg), D2 (4 kg). Each treatment was repeated 3 times so that there were 27 beds in total, each bed consisting of 4 sample plants, so that the total number of plants was 108 plants. The results showed that soaking cucumber seeds using PGPR could increase growth well with a soaking time of 6 hours including: plant height, number of leaves, number of segments. In the generative phase, soaking seeds using PGPR can increase growth by observing the number of flowers. The treatment of chicken manure doses has an effect on plant growth and yield in the 4 kg treatment including: plant height, number of leaves, number of internodes, and number of flowers. The best combination of treatment on the growth of cucumber seeds soaking using PGPR and chicken manure doses is in the W2D2 treatment, namely 6 hours of seed soaking and 4 kg of fertilizer dose. Soaking seeds with a combination of chicken manure can increase vegetative and generative plant growth.